1996
DOI: 10.1136/oem.53.5.312
|View full text |Cite
|
Sign up to set email alerts
|

Dust exposure, respiratory symptoms, and longitudinal decline of lung function in young coal miners.

Abstract: Objectives-To study the role of dust exposure on incidence of respiratory symptoms and decline of lung function in young coal miners. Methods-The loss of lung function (forced vital capacity (FVC), forced expiratory volume in one second (FEV,), forced expiratory flow (MEF), carbon monoxide transfer factor (TLCO)) with time and the incidence of respiratory symptoms in 909 Sardinian coal miners (followed up between 1983 and 1993 with seven separate surveys) has been compared with the past and current individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Carta P et al (1996) [11] studied role of dust exposure on incidence of respiratory symptoms and decline of lung function in young coal miners In logistic models, dust exposure was significant predictor of the onset of respiratory symptoms and decline in lung function. Also Jain B.L.…”
Section: Discussionmentioning
confidence: 99%
“…Carta P et al (1996) [11] studied role of dust exposure on incidence of respiratory symptoms and decline of lung function in young coal miners In logistic models, dust exposure was significant predictor of the onset of respiratory symptoms and decline in lung function. Also Jain B.L.…”
Section: Discussionmentioning
confidence: 99%
“…Some early studies concluded that there was little or no abnormality of pulmonary function in the miners without complicated CWP [Higgins and Oldham, 1962;Rogan et al, 1973;Calvert et al, 1991], and simple CWP was not associated with any respiratory symptoms [Morgan, 1982]. However, there has been growing evidence from both cross-sectional and longitudinal studies to suggest that significant impairment of pulmonary function and occurrence of respiratory symptoms may be associated with exposure to coal mine dust, irrespective of the presence of complicated CWP [Marine et al, 1988;Seixas et al, 1993;Carta et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Carta et al [1996] reported that even moderate exposures to mixed coal-mine dust significantly affected lung function and symptom incidence among underground miners. We evaluated symptoms and lung function among the study miners in order to detect evidence of the effectiveness of respirators under current mining conditions, taking into account smoking, and other factors.…”
Section: Discussionmentioning
confidence: 98%